Impact of extrinsic tongue muscle invasion on stage migration in AJCC 8th edition staging of oral cavity carcinoma. (November 2020) - Marchiano, Emily J.; Mathis, Noah J.; Bellile, Emily L.; Lobo, Remy; Ibrahim, Mohannad; Smith, Joshua D.; Birkeland, Andrew C.; Casper, Keith A.; Malloy, Kelly M.; Swiecicki, Paul L.; Worden, Francis P.; Mierzwa, Michelle L.; et al.
Highlights: EMI's remains a critical component of risk stratification in oral cavity cancer. EMI's impact on survival may not be accurately reflected in the current staging system. Integration of EMI and bone invasion enhances staging stratification in oral cavity cancer.